Estudo da dinâmica de alguns modelos antiferromagnéticos unidimensionais. - Leonardo dos Santos Lima (2009)
We present the low-temperature dynamic properties of the quantum one-dimensional Heisenberg antiferromagnet with integer Spin S with spin-phonon interaction, Dzyaloshins-kii-Moriya interaction and taking into account three magnon processes. First, we present the low-temperature dynamic properties of the quantum one-dimensionalHeisenberg antiferromagnet with integer spin S coupled to phonons. The calculation of the relaxation function is performed using the combination of the memory function formalism with the modified spin-wave theory. The procedure includes up to two-magnon and magnon-phonon processes. We show that the magnon-phonon coupling smooths the double-peak structure obtained for the model in the absence of phonons, when the wavevector q moves from q = ¼. After that, we present a calculation of the in-plane dynamical structure factor for the S = 1 one-dimensional antiferromagnet with a Dzyaloshinskii-Moriya interaction using the Schwinger boson mean-field theory. Then, we present the dynamical properties of the Heisenberg antiferromagnet takinginto account three magnon processes. We calculate the correlation function in time using the modified spin-wave theory. The procedure here includes up to two and three-magnon processes. We show that the double peak structure obtained for the model taking into account two-magnon processes is not smoothed when we take account three-magnon processes too